Cause-Effect Analysis in the Public University: The Case of the Universidad Michoacana de San Nicolas de Hidalgo - García-Huerta, Sergio; Kido-Cruz, Antonio (Unidad Editorial UPTC, 2022)
The problem addressed in this article is related to the valuation of resources (human, economic, technological and methodological) within the Universidad Michoacana de San Nicolás de Hidalgo (UMSNH) in a system of causes and effects of the teaching-learning process of higher education. The objective is to understand synergies in a public university through the participation of key actors within its functions. In order to evaluate the opinions of the experts, human resources from various roles and dependencies of the UMSNH were integrated. The methodology derived from the theory of forgotten effects developed by Kaufmann and Gil-Aluja was used. Six causes and six effects were integrated to be analyzed and it was found that the importance given between "authorities and unions" with "research and innovation" was not initially considered relevant by the participants, but the forgotten effects method indicates that this relationship exists and that this same interpretation occurs in relation to "educational coverage". JEL Codes: A12, B29; D91 Received: 01/11/2021.  Accepted: 04/04/2022.  Published: 01/06/2022.